The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1107/s1600576716018057
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of multigrain indexing for orthorhombic polycrystals above 1 Mbar: application to MgSiO3 post-perovskite

Abstract: This paper describes a methodology for characterizing the orientation and position of grains of an orthorhombic polycrystalline material at high pressure in a diamond anvil cell. The applicability and resolution of the method are validated by simulations and tested on an experimental data set collected on MgSiO 3 post-perovskite at 135 GPa. In the simulations, $95% of the grains can be indexed successfully with $80% of the peaks assigned. The best theoretical average resolutions in grain orientation and positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Generally speaking, the orientations and magnitudes of deviatoric strain are not overly sensitive to factors like the quality of detector calibration and the instrument’s stability. The measured centroidal positions and hydrostatic strains, however, are sensitive and thus more challenging to determine accurately ( 36 ). The size of the rotation range increases accuracy globally, as it leads to both more independent Bragg reflections and more variation in projection directions; this limitation is made apparent in the case of fp in this study, where after extended heating, hundreds of unique orientations were identified, but only a limited number could be constrained spatially.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the orientations and magnitudes of deviatoric strain are not overly sensitive to factors like the quality of detector calibration and the instrument’s stability. The measured centroidal positions and hydrostatic strains, however, are sensitive and thus more challenging to determine accurately ( 36 ). The size of the rotation range increases accuracy globally, as it leads to both more independent Bragg reflections and more variation in projection directions; this limitation is made apparent in the case of fp in this study, where after extended heating, hundreds of unique orientations were identified, but only a limited number could be constrained spatially.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multigrain crystallography (MGC) was developed for in situ diamond anvil cell (DAC) experiments [Nisr et al, 2012;Zhang et al, 2013;Nisr et al, 2014;Langrand et al, 2016]. The method allows in situ measurements of crystallographic structures, grain orientations, and grain statistics at high pressure during dynamic processes such as deformation or phase transformation [Rosa et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we use MTEX Mainprice, Bachmann, Hielscher, Schaeben, & Lloyd, 2015) in order to fit an orientation distribution function (ODF) to the list of single-grain orientations and plot the results as pole figures. Estimated errors in the grain orientations are typically below 0.4° in simulated datasets (Langrand et al, 2017) and they are not expected to exceed 1-2° for real data here.…”
Section: Mgc Experiments and Analysismentioning
confidence: 76%
“…We provide, here, a short description of the MGC data analysis procedure. Details can be found in Langrand et al (2017). We used the open-source software package FABLE-3DXRD (https://github.com/FABLE-3DXRD) complemented with our custom scripts from the TIMEleSS-MGC-tools (https://github.com/FABLE-3DXRD/ TIMEleSS).…”
Section: Mgc Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation